PRECONDITIONS OF LAND RELATIONS DEVELOPMENT: ECONOMIC, LEGAL AND INSTITUTIONAL - Natalia Wasilewska; Tetiana Kaminska (Polityki Europejskie, Finanse i Marketing)
This paper discusses the issues related to the implementation of the land reform in Ukraine. The purpose of the research is to work out a system of measures aimed at developing land relations, in particular, the introduction of the land market in Ukraine, as well as determining the economic impact of the effective turnover of land plots. The analysis of the economic situation in Ukraine over the past 10 years has been carried out. Issues related to land legislation, in particular land valuation, are briefly identified. The institutions without functioning of which the introduction of the land market is impossible, are established. The conducted analysis gave basis to the proposal of preconditions of economic, legal and institutional character, necessary for the successful development of land relations. The article also proposes mortgage refinancing mechanism through the issue of mortgage land securities.